(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The territory of the projected local botanical reserve “Vovchi Vody” is situated in the eastern vicinity of Vovchansk town (Chuhuiv (formerly Vovchansk dist.) district, Kharkiv region, Ukraine) and occupies 47 ha. The area of the perspective nature reserve t includes chalk outcrops, steppe plots, floodplain meadows on the right bank of Vovcha river, spontaneous dumps, roads and trails, ruined buildings of brick factory. There are few finds of rare species, but have not detail floristic researches. The brick factory was working there from the end of XIX to the end of XX centuries. The landscapes are transformed and destroyed after it activity. During 2018–2020, we has thirteen expeditions. We created an annotated list of the vascular plant of the studied territory. The list includes the information about modern scientific name of the species; their relative occurrence; distribution pattern, hyhromorphes and ceonorphes;selection division to alien and rare flora fractions etc. The floristic list of the perspective botanical reserve “Vovchi Vody” includes 206 species from 47 families, 3 classes and 2 divisions of vascular plants. The largest families are Asteraceae (35 species; 16,9 %), Poaceae (20 species; 9,7 %), Fabaceae (20 species; 9,7 %), Lamiaceae (19 species; 9,2 %), Scrophulariaceae (13 species; 6,3 %), Rosaceae (9 species; 4,3 %) Ranunculaceae (7 species; 3,4 %), Apiaceae, Boraginaceae, Rubiaceae (each one contains 6 species; 2,9 %). The area of perspective nature reserve has great scientific and bioconservation importance. Twenty five species have a sozological value. Ten species are included to Red Data Book of Ukraine and fifteen species are included to Оfficial list of regional rare plant species of Kharkiv region.